Identification of molecular markers for an efficient leaf rust resistance gene (Lr29) in wheat - Tar, Melinda (Acta Biologica Szegediensis, 2002)
The aim of this study was to find molecular markers (RAPD and SCAR) for the wheat leaf rust resistance gene Lr29. Among 81 RAPD primers tested, only one (OPYIO) detected an additional band in the resistant NIL of Lr29. The genetic linkage of this molecular marker to Lr29 was tested on a segregating F2 population derived from a cross between the leaf rust resistant line and the susceptible parent GK Délibáb. This marker was closely linked to the Lr29 gene. The polymorphic band was cloned and sequenced. Specific primers (SCAR) were synthesized and after amplification only resistant lines showed an amplified product. A second SCAR primer for another Lr29 RAPD fragment (UBC219, Procunier et al., 1995) was also designed and tested.